Self reported risk reduction behavior associated with HIV counseling and testing: - Mulogo, Edgar Mugema; Abdulaziz, Aden S.; Guerra, Ranieri; Bellows, Ben; Baine, Sebastian O (AIDS care, 2013)
Home-based human immunodeficiency virus (HIV) voluntary counseling and testing (VCT) in Uganda is being promoted to increase coverage, in addition to main stay approach of service provision through health facilities. The aim of this study was to compare self reported risk reduction behavior among clients receiving facility and home-based HIV VCT within a rural context. Pre-post intervention client surveys were conducted in November 2007 (baseline) and March 2008 (follow up) in southwestern Uganda. The facility-based VCT intervention was provided to 500 clients and home-based VCT to 494 clients at baseline, in 2 different sub-counties. A total of 76% (759/994) of these clients were interviewed at the follow up visit. The respondents who received facility-based VCT were more likely to report abstinence (adjusted Odds Ratio [aOR] 1.47, 95% CI 1.074, 2.02), reducing multi sexual relationships (aOR 3.23, 95% CI 2.02, 5.16) and more frequent use of condoms (aOR 3.14, 95% CI 1.60, 6.18). However, they were less likely to report, discussing HIV (aOR 0.63, 95% CI 0.46, 0.85) with their sexual partner/s and having sex with only one partner (aOR 0.72, 95% CI 0.5190.99). While facility-based VCT appears to promote abstinence and condom use home-based VCT on the other hand promotes faithfulness and disclosure. VCT services should, therefore, be provided through both models in a complementary relationship and not as surrogates within given settings
A comparative analysis of facility- and home-based models in rural Uganda
Keywords: Risk reduction behavior; Facility and home-based VCT; Uganda